Bohaterowie azylu dyplomatycznego czasów rewolucji węgierskiej w „Dziennikach” Sándora Máraiego - Czubik, Paweł (PRAWO i WIĘŹ, 2026)
The aim of this article is to present asylum cases (including lesser-known ones) involving the use of diplomatic asylum that took place during the Hungarian Revolution of 1956. At the same time, the text analyzes the assessment of these cases through the prism of the observations of the leading Hungarian émigré writer and poet Sándor Márai. He is currently one of the most famous Hungarian artists in Poland (his works have been made widely available to Polish readers by the Czytelnik publishing house). Márai observed the Hungarian Revolution while living in the US at the time, and for obvious reasons, he was deeply affected by these events. He included his assessment of the heroes of this revolution (primarily Imre Nagy and Cardinal József Mindszenty) in excerpts from his “Diaries”. This assessment is quite critical, especially towards Prime Minister Nagy. Undoubtedly, Sándor Márai judges him to be a communist, has no faith in his “conversion”, does not sympathize with him, and considers the tragic twists and turns of his fate to be gangster-like reprisals by the communists. On the other hand, he perceives Cardinal Mindszenty differently, but does not believe in his intellectual or political abilities. He does not appreciate his religious attitude. However, he does appreciate his behavior, which secured him a rightful place in history.